2010
DOI: 10.1299/jfst.5.317
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of Tip Clearance Effects in Axial Flow Turbines

Abstract: The present study aims to control the leakage flow and total pressure loss in high pressure turbines. A new tip shape is proposed. It is based on the triple squealer shape by adopting a new middle squealer, along the camber line, whose first and last thirds were removed. An unstructured, finite volume, multiblock, 3-D, compressible Reynolds-Averaged Navier-Stokes equations solver was used to compute the flow through a high pressure turbine cascade. The turbulent viscosity was calculated by the Delayed Detached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The pressure arm of tip leading edge horseshoe vortex (PHV) can be identified by blue streamlines, and the suction arm of tip leading edge horseshoe vortex (SHV) can be identified by black streamlines. These vortexes have also been reported in previous studies [31,32]. The SHV moves along the suction side edge, and then exits in a certain distance to shear with the mainstream.…”
Section: Effect Of Winglet Width On Efficiencysupporting
confidence: 85%
“…The pressure arm of tip leading edge horseshoe vortex (PHV) can be identified by blue streamlines, and the suction arm of tip leading edge horseshoe vortex (SHV) can be identified by black streamlines. These vortexes have also been reported in previous studies [31,32]. The SHV moves along the suction side edge, and then exits in a certain distance to shear with the mainstream.…”
Section: Effect Of Winglet Width On Efficiencysupporting
confidence: 85%
“…Liao et al [54] analyzed the internal flow in a Kaplan turbine runner with the Triangle Acute Clearance. Control of the leakage flow by modifying the blade tip shape has been the main subject for much research [55]. Actually cavitation easily occurs in the tip clearance, so two-phase cavitation model should be taken into account in the CFD approach.…”
Section: Cfd In Tip Clearancementioning
confidence: 99%
“…Reducing the negative effects of the tip leakage is generally referred to as tip desensitization. The desensitization methods include active and passive methods [55]. The latter is the major form in hydraulic turbines.…”
Section: Better Design or Optimizationmentioning
confidence: 99%
“…The blade profile is the same as the tip section of NASA/GE Energy Efficient Engine (GE-E 3 ) first-stage rotor blade because results of several studies have been reported regarding it and were used to validate the numerical code. 8,9,[13][14][15][16][17] Calculations were performed for a three-times scaled-up model in the same way as El-Ghandour et al 13,14) and Yang et al 16) This scaled-up model has an axial chord of 86.1 mm (Cx = 86.1), a span of 122 mm (h = 122), and an aspect ratio (span/chord) of 1.4. The blade model is two-dimensional with the same profile in the span direction.…”
Section: Model In Studymentioning
confidence: 99%